Pengelolaan Sarana dan Prasarana Efektif dan Transparan di Lembaga PAUD - Klaudia, Naja (Lembaga Yasin AlSys, 2026)
Financial management of facilities and infrastructure is a critical component of early childhood education (PAUD) administration, as it directly affects service quality and institutional sustainability. Effective and transparent financial management is essential to ensure that PAUD institutions can provide facilities and infrastructure that are adequate, safe, and aligned with national early childhood education standards. This study aims to analyze the principles, strategies, and implementation of effective and transparent financial management of facilities and infrastructure in PAUD institutions. A descriptive qualitative review method was employed, drawing on recent literature, technical regulations, and national and international research on PAUD management. The findings indicate that effective and transparent financial management must be supported by participatory budget planning, accountable reporting, continuous supervision, and the involvement of all stakeholders, including teachers, school committees, and parents. Budget transparency has a positive impact on public trust and on improving PAUD facilities and infrastructure, thereby creating a safe and appropriate learning environment that supports children’s optimal growth and development. The study underscores the importance of financial governance grounded in accountability, efficiency, and openness as the basis for strengthening professional, quality-oriented management of PAUD institutions.